The Combined Effects of Financial Derivatives and Discretionary Accruals on the Value Relevance of Earnings and the Book Value of Equity - Etty Murwaningsari; Sidharta Utama; Hilda Rossieta (Gadjah Mada International Journal of Business, 2015)
This study aimed to understand (1) the association between the use of discretionary accruals and financial derivatives, taking into consideration the implementation of revised PSAK 55 (1999), which was adopted from SFAS 133; (2) the combined effects of derivatives and discretionary accruals on the value relevance of earnings and equity. The analysis used panel data regressions and the Wald test over the period from 2001-2008. The results showed a positive or complementary association between derivatives and discretionary accruals. The positive association implied that managers tended to intensify the use of discretionary accruals to offset a higher use of derivatives. Price and return models demonstrated negative significant effects of derivatives on the value relevance of earnings. The return model showed negative significant effects of discretionary accruals on the value relevance of earnings but negative effects on the value relevance of equity with the price model.